American horror story. Freak show. The complete fourth season / Brad Falchuk Teley-Vision ; Ryan Murphy Productions ; 20th Century Fox Television ; created by Ryan Murphy and Brad Falchuk. - Murphy, Ryan, 1965-; Falchuk, Brad (Twentieth Century Fox Home Entertainment, 2015)
Elsa Mars is the proprietor of a troupe of human "curiosities" on a desperate journey of survival in the sleepy hamlet of Jupiter, Florida, in 1952. Her menagerie of performers includes a two-headed, telepathic twin, a take-charge bearded lady, a vulnerable strongman, and his three-breasted wife. But strange emergence of an entity will savagely threaten the lives of the townsfolk and freaks alike.
Title from disc surface.
All language options may not be listed on container packaging.
Widescreen (1.78:1)
Special features: Getting freaky: a peek inside the tent; Two heads are better than one; Twisty: behind the mask of terror; Freaklore: the spectre of Edward Mordrake; American horror story: freak show extra-ordinary artists; The premiere.
Keywords: Curiosities and wonders -- Drama.; Sideshows -- Drama.; Freak shows -- Drama.; Monsters -- Drama.; Circus performers -- Drama.; Circus performers.; Curiosities and wonders.; Freak shows.; Monsters.; Sideshows.; DVDs.; DVD-Video discs.; Videodiscs.; Drama.; Fiction television programs.; Horror television programs.; Television series.; Video recordings for the hearing impaired.; Thrillers (Television programs); Materiales en español -- Bilingüe.